Building innovation networks in sciencebased young firms : the selection of knowledge sources - Sousa, Cristina (2012)
The paper investigates the strategic choices made by young science-based firms’ regarding the selection of knowledge sources. Drawing on two streams of research – on alliances and on social networks – two different dimensions of this strategy are considered: the activation of the entrepreneurs’ social capital (versus the intentional inclusion of new knowledge sources) and the persistence of ties from start-up to the early growth phase. The data collected for a subset of the Portuguese biotechnology sector are analysed with a view to answer to four research questions: i) To what do extent firms’ rely on entrepreneurs’ personal networks, activating their social capital to access scientific and technological knowledge at start-up; ii) To what extent are new actors added to knowledge networks at start-up; iii) Are there differences between existing and new ties in terms of strength and formalisation?; iv) Is there tie persistence in knowledge networks between the start-up and the early growth phases? The results obtained confirm the consideration of the strategies underlying network building is vital for an understanding of the configuration of young science-based firms’ knowledge networks. They reveal the existence of different network building strategies and appear to indicate a tendency for continuity of attitudes over the companies’ life. They also suggest that differences in the network building strategies may be the behind the somewhat contradictory results presented in the literature about the network configuration that is more favourable for innovation